STUDYING TENSILE STRENGTH FOR EPOXY COMPOSITESREINFORCED WITH GLASS FIBERS - Hammed, Mohammed; Khalaf, Hazim (Iraqi Journal of Science, 2024)
This research includes the studying of tensile resistance for compositematerials reinforced with glass fibers (E-glass). Epoxy resin was used as matrix for thereinforced materials that consist of artificial glass fiber layers (woven roving) withdirectional 0-90 and with the random direction. The sheets made of composite materialswith a number of layers for both types of glass fibers with volume fraction 40% forreinforced materials. All these sheets were cut into samples with measurement 10X120mm and with sample thickness dependent on the number of layers of glass fibers.Tensile resistance test samples were cut to study tensile resistance for these compositematerials. The results and laboratory examinations for these composites show increasingthe tensile resistance values for composites reinforced with glass fibers (woven roving)compared to the composites reinforced with glass fibers with the random direction.